2003
DOI: 10.1016/s0263-8231(02)00085-x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of structural behaviour of transmission towers

Abstract: Transmission towers are a vital component and management needs to assess the reliability and safety of these towers to minimise the risk of disruption to power supply that may result from in-service tower failure. Latticed transmission towers are constructed using angle section members which are eccentrically connected. Towers are widely regarded as one of the most difficult form of lattice structure to analyse. Factors such as fabrication errors, inadequate joint details and variation of material properties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(30 citation statements)
references
References 7 publications
0
27
0
3
Order By: Relevance
“…Results from actual full-scale tower tests indicate that linear static analysis is not consistent in modelling the behaviour of the structure. It is also reported that bending stresses in the members, which initially were assumed to be negligible, can be as high as the axial stresses [27][28][29][30][31]. Ref.…”
Section: Lattice Towersmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from actual full-scale tower tests indicate that linear static analysis is not consistent in modelling the behaviour of the structure. It is also reported that bending stresses in the members, which initially were assumed to be negligible, can be as high as the axial stresses [27][28][29][30][31]. Ref.…”
Section: Lattice Towersmentioning
confidence: 99%
“…Albermani and Kitipornchai [28] present an analytical technique that takes into account both geometric and material non-linearities. The geometric non-linearity analysis considers the effects of accumulated stresses and the effect of the changes in the geometry on the structural stiffness of the elements as the load is increased.…”
Section: Lattice Towersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, full scale transmission tower tests have shown that bending stresses in some members can be as high as axial stresses (Albermani & Kitipornchai, 2003), and that nonlinear effects should be taken into account (Albermani, et al, 2009). …”
Section: Structure Assessment Philosophy and Modelling Strategymentioning
confidence: 99%
“…Most of transmission tower structures are constructed by thin-walled angle members that are eccentrically connected to each other by bolts directly or through gusset plates. In the global analysis of a transmission tower, its angle members are often modeled using either pin-ended truss elements or fix-ended beam elements to form a global finite element (FE) model for the tower [1][2][3][4][5]. Nevertheless, this kind of global model ignores the effects of joint flexibility, local geometric and material nonlinearity, bolt slippage and deformation on the global behavior of the tower, which make the structural analysis and design of the tower inadequate.…”
Section: Introductionmentioning
confidence: 99%